REPORT ON THE ACCOUNTING RESEARCH ACTIVITIES OF THE AMERICAN INSTITUTE OF CERTIFIED PUBLIC ACCOUNTANTS. - Powell, Weldon (The Accounting Review, 1961)
Abstract This article focuses on a report on the accounting research activities of the American Institute of Certified Public Accountants. The Institute's current approach to accounting research is something new. It originated in a suggestion made by Alvin R. Jennings in October 1957, following which a special committee was appointed to consider the matter. The special committee submitted a report in September 1958, proposing a plan for the organization and operation of the accounting research program and related activities of the Institute. The organization for carrying out research work is made up of two bodies. The first is the Accounting Principles Board. It consists of twenty-one members of the Institute, of whom thirteen are practitioners, three are teachers, three are business men, one is in government service, and one is the director of research of the Institute, Carman G. Blough. The Board is the sole group in the Institute having authority to make or authorize public pronouncements on accounting principles. The Board may make pronouncements on accounting principles which are not based on previously published accounting research studies. If it considers action on a particular matter urgent, it may instruct the Director of Accounting Research to have his staff prepare material for its consideration.